2008
DOI: 10.1111/j.1440-1754.2008.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of care in a tertiary level diabetes clinic: Correlations with diabetes knowledge, clinical outcome and health‐related quality of life

Abstract: Most patients and their parents in the RCH diabetes clinic appear generally satisfied with their diabetes care. The degree of satisfaction of care cannot be presumed according to clinical outcome, diabetes knowledge or HRQOL measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…In the same study adolescents aged >13 years who reported a higher quality of care had lower HbA1c levels 9. However, other studies have not found significant correlations between the satisfaction of young peoples with diabetes care and their HbA1c levels 10–12…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the same study adolescents aged >13 years who reported a higher quality of care had lower HbA1c levels 9. However, other studies have not found significant correlations between the satisfaction of young peoples with diabetes care and their HbA1c levels 10–12…”
Section: Introductionmentioning
confidence: 83%
“…The aim of the present study was to determine the association between the experiences of adolescents and parents with paediatric diabetes care at hospital outpatient departments, and the association between these experiences and the HbA1c level of the adolescents. To our knowledge, only two previous studies have simultaneously assessed the associations between parent experiences, adolescent experiences and clinical outcomes for this patient group,9 12 and none of them were performed in Norway. Based on those previous studies, we hypothesised that there would be a correlation between the perceptions of parents and the adolescents about the quality of outpatient care, but no correlation with the HbA1c level.…”
Section: Introductionmentioning
confidence: 99%
“…Patient satisfaction is an integral part of caring for children with diabetes that has been shown to underpin adherence to treatment regimes, though in one metropolitan study (13) it was not associated with improved clinical outcome. Our patients showed improved glycemic control with a parallel improvement in patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Age (please circle) under 13, (parent to complete) 13 2. I feel more supported by a "team" approach 1 2 3 4 5…”
Section: Appendixmentioning
confidence: 99%
“…Outro estudo que avaliou o dispositivo para cálculo da dose de insulina, não o correlacionou com a QVRS, mas permitiu verificar que erros constantes nos cálculos acontecem (100) . (101) .…”
Section: Qvrs E Tratamento Do Dmunclassified